Investasi sebagai Alat untuk Perencanaan Keuangan Masa Depan - Praditya, Raffi Dwi; Safrudin, Safrudin; Ramadhan, Ahmad Rifai; Bahtiar, M. Yusuf (PENG: Jurnal Ekonomi dan Manajemen, 2026)
Planning financial future is an important step in achieving economic prosperity. However, many people still use conventional saving methods without considering the effect of inflation on the value of money. This study aims to analyze investment as an effective tool in long-term financial planning. The research method used is descriptive quantitative research with data collection from questionnaires distributed to respondents aged 20-50 years in the region of Kotabumi, North Lampung. Sampling technique uses purposive sampling with data analysis using descriptive statistics and correlation. The results show that investment plays an important role in improving financial future planning preparation especially through protection against inflation, passive income creation, and long-term financial goals achievement. In addition, understanding the type of investment instruments and risk management also influences individual decisions in investing. Hence, enhancing investment literacy becomes an essential factor to encourage individuals in creating effective financial planning.